2022
DOI: 10.3390/ani12081028
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Two Injection Techniques in Combination with the Local Anesthetics Lidocaine and Mepivacaine for Piglets Undergoing Surgical Castration

Abstract: The present study evaluated the effects of two injection techniques in combination with lidocaine or mepivacaine for piglets undergoing castration. To improve ease of use, a cannula with side holes (one-step fenestrated (F)) was invented to simultaneously deliver a local anesthetic into the testis and scrotum and was compared to a two-step injection technique. The distribution of a lidocaine/contrast agent mixture using the two methods was examined using computed tomography. Piglets were randomly divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…The results from this study agree with numerous studies that have consistently demonstrated lidocaine does not decrease cortisol concentrations in castrated piglets ( 34 36 ) and in fact may increase cortisol concentrations when compared to castrated piglets receiving no anesthetic ( 37 , 38 ). However, past work conducted ( 39 , 40 ), and more recent studies in 2022 ( 41 ) have demonstrated lidocaine efficacy in mitigating castration stress. There seems to be no consensus in the literature about the effectiveness of lidocaine in reducing the physiological responses in piglets undergoing castration, however, this can be explained by differences in the interval between treatment administration and castration (0, 3, 5, 10, or 20 min).…”
Section: Discussionmentioning
confidence: 99%
“…The results from this study agree with numerous studies that have consistently demonstrated lidocaine does not decrease cortisol concentrations in castrated piglets ( 34 36 ) and in fact may increase cortisol concentrations when compared to castrated piglets receiving no anesthetic ( 37 , 38 ). However, past work conducted ( 39 , 40 ), and more recent studies in 2022 ( 41 ) have demonstrated lidocaine efficacy in mitigating castration stress. There seems to be no consensus in the literature about the effectiveness of lidocaine in reducing the physiological responses in piglets undergoing castration, however, this can be explained by differences in the interval between treatment administration and castration (0, 3, 5, 10, or 20 min).…”
Section: Discussionmentioning
confidence: 99%
“…In part 2, 2 injection techniques were applied with 1 selected local anesthetic on 47 piglets from 10 litters. In part 3, the most effective local anesthetics and injection techniques identified in the first two parts were used [10][11][12]. In addition, local anesthesia in part 3 was combined with systemic analgesia.…”
Section: Experimental Designmentioning
confidence: 99%
“…The piglets of the sham group (handling only) were also fixed in the castration stand, and an injection was simulated by pressure exerted with the needle cap while the testicles were fixed with the fingers. The one-step fenestrated injection technique (one-step [F] injection) used for comparison in parts 2 and 3 was carried out with a 25-gauge needle (0.5 × 10 mm) that had four lateral openings in addition to the distal opening, two of them proximally and two distally [12]. Thus, during injection, the local anesthetic was simultaneously administered distally into the testicle and proximally into the subcutis of the scrotum.…”
Section: Castrationmentioning
confidence: 99%
“…The expression of c-FOS and FOS in neurons of the spinal cord is an established marker to quantify neural activity in response to noxious stimulation postmortem [ 25 , 26 ]. It was applied in pigs as well, and single studies have evaluated FOS expression to investigate pain or nociception, respectively, following piglet castration [ 27 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%